Wear and damage in retrieved humeral inlays of reverse total shoulder arthroplasty: Where, how much, and why? - Müller, Ulrike; Harzi, Amal; Löscher, Raphael; Bülhoff, Matthias; Eckert, Johannes A.; Kretzer, Jan Philippe (Journal of shoulder and elbow surgery, 2021)
Background - Polyethylene (PE) wear and material degradation have been reported as complications in reverse total shoulder replacements (rTSAs). In this regard, scapular notching is associated with more clinical complications. Therefore, the purposes of the study were to quantify the linear and volumetric wear, as a measure for the amount of removed material, and to qualitatively assess the PE damage modes to describe the material degradation in retrieved rTSA humeral PE inlays that contribute to failure of shoulder replacements. Furthermore, this study aimed to evaluate the effect of scapular notching on PE wear and rim damage of the humeral components. - Methods - The total study population of 39 humeral inlays contains 2 cohorts that were used for the damage mode analysis and for the wear analysis, respectively. The extent and presence of wear damage modes in 5 defined zones were assessed by a grading system for all PE joint replacements. For quantitative wear analysis the most frequent design (n = 17) was chosen. Using a coordinate-measuring machine and postprocessing software, volumetric wear measurements for the retrieved humeral PE inlays were undertaken. Furthermore, prerevision radiographs were analyzed for scapular notching. Finally, retrieval findings were correlated with clinical and radiographic data to consider the effect of notching and to identify risk of failures for these prostheses. - Results - Damage on the rim of the humeral PE inlays was more frequent and severe than on the intended articulation surface. Irrespective of the damage mode, the inferior rim zone sustained the greatest amount of wear damage followed by the posterior zone. Burnishing, scratching, pitting, and embedded particles are most likely to occur in the articular surface area, whereas surface deformation, abrasion, delamination and gross material degradation are predominantly present in the inferior and posterior rim zones. The retrieved inlays exhibited a mean volumetric wear rate of 296.9 mm³/yr ± 87.0 mm³/yr. However, if the notched and non-notched components were compared, a significant higher volumetric wear rate (296.5 ± 106.1 mm³/yr) was found for the notched components compared to the non-notched group (65.7 ± 7.4 mm³/yr). Generally, there was a significantly greater incidence of damage and greater amount of wear if scapular notching occurred. - Conclusion - The notched components showed a 5-fold increase in PE wear rate. Therefore, scapular notching has a strong effect on PE damage and wear. If scapular notching can be clinically avoided, the PE wear performance is in a similar magnitude as found for hip and knee replacements.
Gesehen am 09.09.2021
First published: 19 November 2020